The Art of Kelarai in Malay Architecture - Nur Syahidah Taufik; Harlina Md Sharif Sharif; Rajabi Abdul Razak (International Journal of Environment, Architecture, and Societies, 2022)
Kelarai is defined as checkered weave patterns, a craftwork that has been passed down from generation to generation in Malay culture and people in Southeast Asia. Since its beginning, the arrangement of simple patterns has now grown into many unique kelarai designs with different making techniques or weaving techniques applied for each kelarai. Kelarai is utilized in various products, from everyday items like mats and food covers to decorative elements seen in traditional architecture, like walls and windows. People today can still recognize the art of kelarai on daily basis products. However, only a few have seen or even know about the use of kelarai in traditional architecture. With only a few kelarai craftsmen and evidence of kelarai architecture left, the art of kelarai wall is also at risk of vanishing. Therefore, this study aims to document the varieties of kelarai in traditional architecture, the methods of making kelarai from kelarai craftsmen, and to identify the techniques used in kelarai walls of traditional architecture. An interview and participatory observation are conducted with kelarai craftsman to collect data. Site visits to case studies locations, visual documentation, and analysis through online search are undertaken to learn more about the remaining traces of kelarai architecture. The study is significant in the diminishing kelarai architecture area due to a lack of written documentation and awareness. The study will also contribute to the urgency of preserving the remaining kelarai architecture, which is gradually deteriorating and awaiting demolition.